Cooperatives in the rural sector for the productive reintegration of the demobilized - Lora Ochoa, Carmen; Pinedo López, Jhon William; Burgos Salvador, Marysol (Cooperativismo & Desarrollo, 2017)
Purpose: The central objective of this study is to analyze if there is a favorable social, economic and legal scenario to establish rural cooperatives as an option for the productive insertion of demobilized people in Colombia’s post-conflict and to improve the quality of life of the countryside’s inhabitants. Methodology: A rigorous analysis of documents, norms, programs and economic data on cooperativism, rural development and reintegration in Colombia was performed. The impact of cooperatives in other geographical contexts was also studied. Development: The study’s starting point lies in the social and economic uncertainty generated by the reintegration process, both for the demobilized and the rest of society. The methodology is analytical and propositional because it analyzes the context and proposes rural cooperativism as an alternative to provide solutions in terms of social, labor and productive reintegration. Conclusions: There is an appropriate scenario for rural cooperatives to contribute to the increment of national production and agricultural products’ import reduction, especially in those cases with comparative advantages and which currently represent a trade deficit in the country’s balance of payments.